Droop Characteristics of Doubly Fed Induction Generator Energy Storage Systems within Micro Grids - K.L. Sireesha; G. Kesava Rao (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This article presents the operation of DFIG Doubly fed induction generator and a component energy storage (ES) within micro grids (MG). The aim of this proposal is to control voltage and frequency of wind farm micro grid shared by the Doubly fed induction generator (DFIG) through droop characteristics. This paper is mainly concerned with the operation of islanded micro grids. The proposed control methods are pretend by using Matlab/simulink.